Determining the Environmental Performance of Indonesian SMEs influence by Green Supply Chain Practices with Moderating Role of Green HR Practices - Kittisak Jermsittiparsert; Parinya Siriattakul; Samanan Wattanapongphasuk (International Journal of Supply Chain Management, 2019)
In today’s globally competitive world the phenomenon of Green Supply Chain Management (GSCM) has emerged and gained attention for environmental concerns around the globe. The research study aims to examine the relationship between GSCM and environment related outcomes among Indonesian manufacturing SMEs. Literature review depicted that there are various important and crucial factors today, important in determining the environmental performance. The current study entails the green HRM practices as moderating effect between dependent and independent constructs of the study. The data was collected by questionnaire from SMEs of Indonesia and examined the collected responses by using SMART-PLS. Interestingly; findings have been shared by the study that green supply chain practices influence the environmental performance. The study found that moderating role of Green HRM was not observed between green purchasing and environmental performance but green HR practices moderate the relationship between green logistics and environmental performance.